Forever trapped in the imaginary of late capitalism? The serialized true crime podcast as a wake-up call in times of criminological slumber. (December 2019) - Yardley, Elizabeth; Kelly, Emma; Robinson-Edwards, Shona
Within this article, we explore the emergence of the serialized true crime podcast through an ultra-realist lens. These representations have become increasingly popular in recent years and appear to embody changing sensibilities towards crime and criminal justice – we critically consider whether serialized true crime podcasts do or could represent a change from the true crime of the past. More importantly, we question the extent to which academic criminology is equipped to engage in critical analysis of this media and address the questions that they raise about crime and society's response to it in late capitalist society.